Efficacy and Safety of Carisbamate in Patients with Diabetic Neuropathy or Postherpetic Neuralgia: Results from 3 Randomized, Double‐Blind Placebo‐Controlled Trials. Issue 4 (22nd May 2013) - Smith, Timothy; DiBernardo, Allitia; Shi, Yingqi; Todd, Mike J.; Brashear, H. Robert; Ford, Lisa M.
Abstract The results of 3 proof‐of‐concept studies to evaluate carisbamate's efficacy and safety in treating neuropathic pain are presented. In studies 1 (postherpetic neuralgia, n = 91) and 2 (diabetic neuropathy, n = 137), patients received carisbamate 400 mg/day or placebo for 4 weeks and then crossed over to the other treatment for 4 weeks. In study 3 (diabetic neuropathy, higher carisbamate doses), patients (n = 386) were randomized (1:1:1:1) to receive either carisbamate 800 mg/day, 1200 mg/day, pregabalin 300 mg/day or placebo for 15 weeks. Primary efficacy end point was the mean of the last 7 average daily pain scores obtained on days the study drug was taken, for all 3 studies. Least square mean (95% CI) differences between carisbamate and placebo groups on the primary end point were as follows: study 1: −0.512 (−1.32, 0.29) carisbamate 400 mg/day; study 2: −0.307 (−0.94, 0.33) carisbamate 400 mg/day; and study 3: −0.51 (−1.10, 0.08), carisbamate 800 mg/day; −0.55 (−1.13, 0.04), carisbamate 1200 mg/day; and −0.43 (−1.01, 0.15), pregabalin 300 mg/day. Neither carisbamate (all 3 studies) nor pregabalin (study 3) significantly differed from placebo, although multiple secondary end points showed significant improvement in efficacy with carisbamate in studies 1 and 2. Dizziness was the only treatment‐emergent adverse event occurring at ≥10% difference in carisbamate groups versus placebo (study 1: 12% vs. 1%; study 3: 14% vs. 4%; study 2: 1% vs. 2%). Carisbamate, although well tolerated, did not demonstrate efficacy in neuropathic pain across these studies, nor did the active comparator pregabalin (study 3).